Pengaruh Lingkungan Kerja Dan Kompensasi Terhadap Kepuasan Kerja Pegawai Pada Dinas Lingkungan Hidup Kabupaten Aceh Timur - Amirullah, Amirullah (Fakultas Ekonomi dan Bisnis Islam, 2019)
Abstract This study aims to determine the effect of the work environment and compensation on employee job satisfaction in the East Aceh Regency Environmental Service, both partially and simultaneously. This research is a quantitative study, the research subjects were all employees at the East Aceh Regency Environmental Service, totaling 55 employees. Data collection using a questionnaire that has been tested for validity and reliability. Data analysis tools use multiple linear regression analysis. The results showed that there was a positive and significant effect between work environment on job satisfaction, there was a positive and significant effect between compensation on job satisfaction, there was a positive and significant simultaneous effect between work environment and compensation on job satisfaction. Keywords: Work Environment, Compensation, and Job Satisfaction.